ANCIENT GREEK RELIGION - Rose, H. J. (Herbert Jennings), 1883-1961. Link ([S.l.])
1 online resource pages cm
Keywords: Ancient Greek Religion (1948) looks at the religious beliefs and practices of classical Greece. Completely different to the religions as practiced today, the religion of ancient Greece had no creed, nothing like a code or system of morality that worshippers had to adhere to; nor was there a system of ecclesiastical authority. These fundamentally different facets are examined, and the picture of ancient religion is clarified and expanded.